Analisis Faktor yang Mempengaruh Pengetahuan Gizi Seimbang pada Anak - Sari, Desty Ebhil Puspita; Lestari, Dwi Indah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the factors that influence children's knowledge of balanced nutrition. The method used is a literature review. This research data was taken from four relevant databases such as PubMed, Science Direct, EBSCO and Google Scholar using the PIOS (Participant, Intervention, Outcomes and Study Design) method. The results of the research show that the data taken are journals published in 2020-2024 in English and Indonesian (open access and full text) as well as original articles. Of the n= 3,252 articles found, only n=10 met the inclusion criteria. This literature review explains that there are several factors that are considered to influence knowledge of balanced nutrition, namely level of knowledge, behavior, attitudes, eating patterns, the role of parents and peers. In conclusion, it can be concluded that several of these factors are very important in order to formulate more comprehensive nursing interventions, which are expected to improve the quality of children's physical, psychological and social health. Keywords: Balanced Nutrition, Knowledge, Dietary Habit